Value of Animal Traceability Systems in Managing Contagious Animal Diseases: Final Report to the Program of Research on the Economics of Invasive Species Management - Schroeder, Ted C.; Pendell, Dustin L. (My University, 2010)
Concerns regarding management of animal disease and related perceptions about food safety have escalated substantially in recent years. Terrorist attacks of September 2001, discovery of bovine spongiform encephalopathy in a dairy cow in December 2003 in Washington state and subsequent discoveries of BSE infected animals in Texas in 2005 and Alabama in 2006, and recent worldwide outbreaks of highly contagious animal diseases (i.e., Foot-and-Mouth Disease and Avian Influenza A (H5N1)) have made apparent the need for animal traceability in U.S. livestock production and marketing. In addition, animal identification and trace back systems are rapidly developing throughout the world increasing international trading standards. This report’s goal is to quantify and evaluate the economic impacts of different depths of animal identification/trace back systems in the event of a hypothetical highly contagious foot-and-mouth disease outbreak that poses a threat to U.S. livestock competitiveness. In addition, this report analyzes the local economic impact of a FMD outbreak under three different disease introduction scenarios. Specifically, an epidemiological disease spread model is used to evaluate the impact of a foot-and-mouth disease outbreak in southwest Kansas. The information obtained from the disease spread model is then integrated with an economic framework.
Keywords: Animal disease; Food safety; Foot-and-Mouth-Disease; Animal identification systems; Animal traceability; Epidemiological model; Kansas